Information culture: a lexical-morphological analysis - Martines, Alexandre Robson [UNESP]; Woida, Luana Maia [UNESP]; Almeida, Carlos Candido [UNESP] (Univ Federal Minas Gerais, Escola Biblioteconomia, 2021)
The Informational Culture was established in the Information Science scenario and its objective is to discuss the cultural values related to information as determining indicators to portray an informational reality. The intent is to understand the informational culture to identify the needs of information, organize the information and the knowledge to set control strategies, intervention, systematization and dissemination of knowledge developed and proposed in contexts and domains in which they are applied. However, there is an important factor to debate about informational culture: the terminology for naming the area. After the creation of the term, the concept began to be exploited in various debates, both within and outside the Information Science, however, because there is a terminological definition, various terms were applied to rescue the concept, factor that resulted in difficulties to rescue research papers. Given this, the purpose of this work is to conduct a linguistic analysis to identify terminology in Linguistics theories that contribute to the adequacy of the best term to the scientific-social scenario and to the semantic constitutions in the structuring of expression, as well as its discursive representation. To this end, a qualitative, exploratory and descriptive research was carried out on the positioning of specialists in the area, as well as on the fundamentals of Morphology to analyze the terminological constitution. In addition, it is understood that it is necessary to recover definitions about the theories involved, if it does not end the discussion about the term, at least, provide structural tools to align with the expectations produced in the scenario about the role it occupies in Information Science.
Keywords: Informational Culture; Lexical-Morphological Analysis; Terminology; Metalinguistic Analysis; Terminology Translation; Discursive Representation